Left ventricular ejection fraction is associated with prevalent and incident cardiovascular disease in patients with intermittent claudication – results from the CAVASIC Study. Issue 2 (April 2015) - Rantner, Barbara; Pohlhammer, Johannes; Stadler, Marietta; Peric, Slobodan; Hammerer-Lercher, Angelika; Klein-Weigel, Peter; Fraedrich, Gustav; Kronenberg, Florian; Kollerits, Barbara
Abstract: Background: Individuals with an impaired ventricular function have a poor prognosis due to underlying heart failure and higher mortality rates. Patients with peripheral arterial disease (PAD) represent a high-risk population for left ventricular systolic dysfunction (LVSD). Methods: The left ventricular ejection fraction (LVEF) was measured in a subset of the CAVASIC Study, consisting of 180 male patients with intermittent claudication and 226 controls. The patients were prospectively followed for a median time of 7 years. The association of LVEF with PAD and prevalent cardiovascular disease (CVD) as well as with incident CVD and survival rates during follow-up was analyzed. Results: The prevalence of LVSD (LVEF<55%) was 30% among PAD patients and 7% among controls (p < 0.001). The adjusted logistic regression analysis showed that a decrease of LVEF by one standard deviation (SD) and an LVEF below 55% was associated with PAD (OR = 1.72, 95%CI 1.30–2.28 and OR = 5.71, 95%CI 2.52–12.95, both p < 0.001). Similar results were found for prevalent CVD (n = 50) in PAD patients: LVEF per SD: OR 1.60; LVEF <55%: OR 2.81, both p ≤ 0.008. The adjustment for ln-NT-proBNP or hs-cTnT resulted in a borderline significant association. In the adjusted Cox regression analysis a decrease of LVEF by one SD showed a trend for association with all-cause mortality (n = 32) (HR 1.27, p = 0.08). An impaired LVEF significantly increased the risk for incident major CVD events (n = 52): HR 1.56, p < 0.01. Conclusions: Patients with PAD have significantly lower LVEF values compared to controls. The LVEF can serve as a risk predictor for subsequent cardiovascular disease among this high-risk population. Highlights: Left ventricular ejection fraction is associated with symptomatic PAD. Left ventricular ejection fraction is associated with prevalent CVD in PAD patients. Left ventricular ejection predicts major incident CVD events in PAD patients. PAD patients should be routinely subjected to transthoracic echocardiography (TTE). TTE could be performed complementary to cardiac markers in PAD risk assessment.